Exploring the Lived Experiences of ELT Teachers: Nepali Teachers’ Voices - Pandey, Dinesh Kumar (Lumbini Journal of Language and Literature, 2024)
This study explores the experiences of Nepali English language teachers teaching English in Nepal, with a special focus on the challenges and transformations they face as learners and educators. Drawing on interviews with four high school teachers from institutional schools in the Kathmandu Valley, the research employs a transformational theoretical framework to transcribe, code, and thematically analyze data. The findings highlight persistent traditional teacher roles and reveal critical challenges, including discriminatory policies, multilingual classroom dynamics, and inadequate pedagogical training. The study also emphasizes the shifting status of English from a foreign to a second language and the influence of pedagogical advancements and technological innovations, particularly during the COVID-19 pandemic. These changes have redefined teachers’ roles, transforming them from knowledge dispensers to guides, mentors, and facilitators.